Răspuns :
[tex]a) $ $ x^2-14x+40 = x^2-10x-4x+40 = x(x-10) - 4(x-10)= \\ = (x-4)(x-10) \Rightarrow\boxed{x_1 = 4,$ $ $ $ x_2 = 10} \\ \\ b) $ $ x^2-13x+40 = x^2-8x-5x+40 = x(x-8)-5(x-8) = \\ = (x-8)(x-5) \Rightarrow \boxed{x_1=8,$ $ $ $ x_2 = 5 } \\ \\ c)$ $ x^2+11x+30=x^2+5x+6x+30 = x(x+5)+6(x+5)= \\ =(x+5)(x+6) \Rightarrow \boxed{x_1 = -5, $ $ $ $ x_2=-6} \\ \\ d) $ $ x^2+9x-10= x^2-x+10x-10 = x(x-1)+10(x-1) = [/tex]
[tex]=(x-1)(x+10)\Rightarrow \boxed{x_1 = 1, $ $ $ $ x_2 = -10} \\ \\ e)$ $ x^2-7x+12 = x^2-3x-4x+12 = x(x-3)-4(x-3)= \\ =(x-3)(x-4) \Rightarrow \boxed{x_1 = 3,$ $ $ $ x_2 = 4} \\ \\ f)$ $ x^2+8x+7=x^2+x+7x+7 = x(x+1)+7(x+1) = \\ =(x+1)(x+7) \Rightarrow \boxed{x_1 = -1, $ $ $ $ x_2 = -7}[/tex]
[tex]=(x-1)(x+10)\Rightarrow \boxed{x_1 = 1, $ $ $ $ x_2 = -10} \\ \\ e)$ $ x^2-7x+12 = x^2-3x-4x+12 = x(x-3)-4(x-3)= \\ =(x-3)(x-4) \Rightarrow \boxed{x_1 = 3,$ $ $ $ x_2 = 4} \\ \\ f)$ $ x^2+8x+7=x^2+x+7x+7 = x(x+1)+7(x+1) = \\ =(x+1)(x+7) \Rightarrow \boxed{x_1 = -1, $ $ $ $ x_2 = -7}[/tex]
a)x²-14x+40=x²-10x-4x+40
=x(x-10)-4(x-10)
=(*x-10)(x-4) =>x₁=10 si x₂=4
b)x²-13x+40=x²-8x-5x+40
=x(x-8)-5(x-8)
=(x-8)(x-5) =>x₁=8 si x₂=5
c)x²+11x+30=x²+5x+6x+30
=x(x+5)+6(x+5)
=(x+5)(x+6) =>x₁=-5 si x₂=-6
d)x²+9x-10=x²+10x-x-10
=x(x+10)-(x+10)
=(x+10)(x-1) =>x₁=-10 si x₂=1
e)x²-7x+12=x²-3x-4x+12
=x(x-3)-4(x-3)
=(x-3)(x-4) =>x₁=3 si x₂=4
f)x²+8x+7=x²+7x+x+7
=x(x+7)+(x+7)
=(x+7)(x+1) =>x₁=-7 si x₂=-1
=x(x-10)-4(x-10)
=(*x-10)(x-4) =>x₁=10 si x₂=4
b)x²-13x+40=x²-8x-5x+40
=x(x-8)-5(x-8)
=(x-8)(x-5) =>x₁=8 si x₂=5
c)x²+11x+30=x²+5x+6x+30
=x(x+5)+6(x+5)
=(x+5)(x+6) =>x₁=-5 si x₂=-6
d)x²+9x-10=x²+10x-x-10
=x(x+10)-(x+10)
=(x+10)(x-1) =>x₁=-10 si x₂=1
e)x²-7x+12=x²-3x-4x+12
=x(x-3)-4(x-3)
=(x-3)(x-4) =>x₁=3 si x₂=4
f)x²+8x+7=x²+7x+x+7
=x(x+7)+(x+7)
=(x+7)(x+1) =>x₁=-7 si x₂=-1